2016
DOI: 10.1074/jbc.m116.719591
|View full text |Cite
|
Sign up to set email alerts
|

DNA Interactions Probed by Hydrogen-Deuterium Exchange (HDX) Fourier Transform Ion Cyclotron Resonance Mass Spectrometry Confirm External Binding Sites on the Minichromosomal Maintenance (MCM) Helicase

Abstract: The archaeal minichromosomal maintenance (MCM) helicase from Sulfolobus solfataricus (SsoMCM) is a model for understanding structural and mechanistic aspects of DNA unwinding. Although interactions of the encircled DNA strand within the central channel provide an accepted mode for translocation, interactions with the excluded strand on the exterior surface have mostly been ignored with regard to DNA unwinding. We have previously proposed an extension of the traditional steric exclusion model of unwinding to al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 53 publications
0
29
0
Order By: Relevance
“…However, emerging lines of evidence are starting to suggest that the lagging strand may wrap around the external surface of the CMG and support helicase activity (Figure 7D). Consistent with this notion, DNA interactions with the external surface of archaeal MCM is integral to helicase function (Rothenberg et al, 2007, Costa et al, 2008, Graham et al, 2011, Graham et al, 2016). DNA binding to the MCM external surface appears at least partially facilitated by the NTD-A region, which can undergo large structural rearrangements to expose a DNA-binding site (Fletcher et al, 2003, Chen et al, 2005, Costa et al, 2008, Miller et al, 2014).…”
Section: Helicase Activationmentioning
confidence: 75%
“…However, emerging lines of evidence are starting to suggest that the lagging strand may wrap around the external surface of the CMG and support helicase activity (Figure 7D). Consistent with this notion, DNA interactions with the external surface of archaeal MCM is integral to helicase function (Rothenberg et al, 2007, Costa et al, 2008, Graham et al, 2011, Graham et al, 2016). DNA binding to the MCM external surface appears at least partially facilitated by the NTD-A region, which can undergo large structural rearrangements to expose a DNA-binding site (Fletcher et al, 2003, Chen et al, 2005, Costa et al, 2008, Miller et al, 2014).…”
Section: Helicase Activationmentioning
confidence: 75%
“…Previously, we have shown that interactions with the excluded strand exist for the 3Ј-5Ј hexameric SsoMCM helicase (11,22). Using a similar smFRET approach, we sought to examine whether analogous contacts on the exterior of EcDnaB also interact with the excluded strand despite the opposing 5Ј-3Ј translocation polarity.…”
Section: Ecdnab Interacts With the Excluded Strandmentioning
confidence: 99%
“…Mutating positively charged residues involved in the excluded strand interaction inhibited SsoMCM's unwinding activity (11,22). Gel-based fluorescent DNA unwinding assays were performed to determine whether these EcDnaB SEW mutants have any effect on activity.…”
Section: Sew Mutants Of Ecdnab Have Enhanced Dna Unwinding Activitymentioning
confidence: 99%
“…In HDX experiments, the exchange rate of backbone amide hydrogens, which is affected by solvent accessibility and possible involvement in hydrogen bonding, can be directly determined by MS analysis. This technique has been broadly employed to study conformational changes [19,20], protein folding [21] and protein-protein interactions [22,23], as well as nucleic acid-protein complexes [24,25,26,27,28,29]. Among the MS3D techniques, chemical and photo-activated cross-linking (XL) are employed to generate stable covalent bridges between contiguous functional groups, which can reveal their mutual placement in the targeted assembly [13,16].…”
Section: Introductionmentioning
confidence: 99%